The Macromolecular Femtosecond Crystallography Instrument at the Linac Coherent Light Source. (22nd February 2019) - Sierra, Raymond G.; Batyuk, Alexander; Sun, Zhibin; Aquila, Andrew; Hunter, Mark S.; Lane, Thomas J.; Liang, Mengning; Yoon, Chun Hong; Alonso-Mori, Roberto; Armenta, Rebecca; Castagna, Jean-Charles; Hollenbeck, Michael; et al.
Abstract : A description of the Macromolecular Femtosecond Crystallography instrument at the Linac Coherent Light Source is given. Scientific capabilities are highlighted, performance parameters are presented along with some commissioning results. Abstract : The Macromolecular Femtosecond Crystallography (MFX) instrument at the Linac Coherent Light Source (LCLS) is the seventh and newest instrument at the world's first hard X‐ray free‐electron laser. It was designed with a primary focus on structural biology, employing the ultrafast pulses of X‐rays from LCLS at atmospheric conditions to overcome radiation damage limitations in biological measurements. It is also capable of performing various time‐resolved measurements. The MFX design consists of a versatile base system capable of supporting multiple methods, techniques and experimental endstations. The primary techniques supported are forward scattering and crystallography, with capabilities for various spectroscopic methods and time‐resolved measurements. The location of the MFX instrument allows for utilization of multiplexing methods, increasing user access to LCLS by running multiple experiments simultaneously.